2016
DOI: 10.1016/j.drugalcdep.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Risky driving and sexual behaviors as developmental outcomes of co-occurring substance use and antisocial behavior

Abstract: PURPOSE To examine the associations between substance use and antisocial behavior trajectories and seven risky behaviors over time. METHOD Data were collected from a high-risk sample of adolescents followed into young adulthood. Five trajectory classes, identified based on dual development of substance use and antisocial behavior symptoms, were used to predict three risky driving and four risky sexual behaviors. RESULTS In this high-risk sample, participants reported notably high overall rates of reckless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
(43 reference statements)
0
16
1
Order By: Relevance
“…Given the vulnerability for alterations in brain structure and function during adolescent age, alcohol may cause neurocognitive, learning and mental health problems ( Feldstein Ewing, Sakhardande, & Blakemore, 2014 ; Marshall, 2014 ). As well, alcohol consumption may alter social and behavioural functioning, leading to emotional difficulties ( Tomlinson, Brown, & Abrantes, 2004 ), comorbid substance use ( Luk et al, 2016 ), violent conduct and risky sexual behaviours ( Komro, Tobler, Maldonado-Molina, & Perry, 2010 ). Besides this, alcohol can be considered as a risk factor for premature mortality among adolescents in Europe ( Inchley et al, 2018 ) due to its potential harmful and adverse consequences, such as unintentional injuries, road-traffic accidents and suicidal behaviours ( Maldonado-Molina, Reingle, Tobler, & Komro, 2010 ; Swahn, Bossarte, Ashby, & Meyers, 2010 ).…”
mentioning
confidence: 99%
“…Given the vulnerability for alterations in brain structure and function during adolescent age, alcohol may cause neurocognitive, learning and mental health problems ( Feldstein Ewing, Sakhardande, & Blakemore, 2014 ; Marshall, 2014 ). As well, alcohol consumption may alter social and behavioural functioning, leading to emotional difficulties ( Tomlinson, Brown, & Abrantes, 2004 ), comorbid substance use ( Luk et al, 2016 ), violent conduct and risky sexual behaviours ( Komro, Tobler, Maldonado-Molina, & Perry, 2010 ). Besides this, alcohol can be considered as a risk factor for premature mortality among adolescents in Europe ( Inchley et al, 2018 ) due to its potential harmful and adverse consequences, such as unintentional injuries, road-traffic accidents and suicidal behaviours ( Maldonado-Molina, Reingle, Tobler, & Komro, 2010 ; Swahn, Bossarte, Ashby, & Meyers, 2010 ).…”
mentioning
confidence: 99%
“…According to the literature, our findings confirm that early sexual debuts (Muindia et al, 2014;Santelli et al, 2000) and risk-taking personality profiles (Lee & Hahm, 2010;Morales-Alemán & Scarinci, 2016) are positively associated with sexual behaviours (RQ2). In particular, the use of drugs and alcohol is strongly related to sexual conduct (Bryan et al, 2012;Guo et al, 2002;Khan et al, 2012;Luk et al, 2016;Ritchwood et al, 2016;Tapert et al, 2001). In line with Irwin (1990), reckless driving is directly associated with occasional sexual partners.…”
Section: Discussionmentioning
confidence: 84%
“…multiple sexual partners, early initiation of sexual intercourse, and not using condoms; Morales-Alemán & Scarinci, 2016). In particular, it was highlighted that binge drinking (Lee & Hahm, 2010) and drug use (Bryan, Schmiege, & Magnan, 2012;Guo et al, 2002;Khan, Berger, Wells, & Cleland, 2012;Luk et al, 2016;Ritchwood, DeCoster, Metzger, Bolland, & Danielson, 2016;Tapert, Aarons, Sedlar, & Brown, 2001) are associated with increased sexual risk behaviours; in addition, it was demonstrated that reckless driving is correlated with alcohol use, substance use, and sexual conduct (Adu-Frema, Saka, & Perrino, 1997;Irwin, 1990;Stanton, Li, Cottrell, & Kaljee, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, its consumption is not seen as a habit to be discouraged or even considered by health professionals (27) . This is a public health issue that must be discussed given the potential health hazards of alcohol consumption (15) and its association with other high-risk behaviors, such as reckless driving and unprotected sex (28) . It would be important to implement a policy of educating students to raise awareness of both health and social problems resulting from the use of substances, especially alcohol, given its high prevalence in this population.…”
Section: Discussionmentioning
confidence: 99%